Toward a Unified Framework: A Study on the Registration of Data Intellectual Property Rights - Chu Lei (Studies in Law and Justice, 2025)
As an important institutional practice in the field of data registration, there are some points of disagreement in theory and practice that need to be harmonized. The object of registration of data intellectual property rights should be data, and the limitations of the object of registration should be three: first, the data should be collected or obtained in accordance with the law; second, the data should be processed by certain rules; third, the data should have practical value. Registration of data intellectual property rights should follow the principle of “limited substantive review” and build a composite review framework. Registration of data intellectual property rights should be given an effect of rights determination, the right holder would hold a new type of intellectual property right upon registration.